2019
DOI: 10.1016/j.ijid.2018.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiological and molecular investigations of infections with Crimean–Congo haemorrhagic fever virus in Kazakhstan

Abstract: The aim of this study was to detect the seroprevalence of Crimean-Congo haemorrhagic fever virus (CCHFV) in patients with fever of unknown origin (FUO) in endemic (Kyzylorda) and non-endemic (Almaty) oblasts of Kazakhstan. Methods: Paired serum samples from 802 patients with FUO were collected. Serum samples were investigated by ELISA to detect IgG and IgM antibodies against CCHFV. Sera with suspected acute infection were further investigated by RT-PCR to detect the viral RNA. Results: IgG antibodies were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 32 publications
(74 reference statements)
1
19
0
Order By: Relevance
“…Russia and western Asia. Georgia shows a prevalence similar to that in eastern European countries (2.8%, [52]), while the Russian Federation (11.1%, [53]) and Kazakhstan (12.7%, [51]) show a prevalence closer to that found in Turkish areas, with a moderate/high prevalence.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 58%
See 2 more Smart Citations
“…Russia and western Asia. Georgia shows a prevalence similar to that in eastern European countries (2.8%, [52]), while the Russian Federation (11.1%, [53]) and Kazakhstan (12.7%, [51]) show a prevalence closer to that found in Turkish areas, with a moderate/high prevalence.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 58%
“…The articles were classified according to their origin in three European regions. The main characteristics of these studies are shown in Tables 1-3: Table 1 The oldest article was published by Horvath et al in 1979 [46], and the most recent was published by Abdiyeva et al in 2019 [51]. All articles were cross-sectional studies (descriptive studies).…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Parallel investigations of the same FUO samples used in this study for other arthropod‐borne infectious showed that some serum samples with confirmed orthohantavirus IgG antibodies were reactive also for other agents: for Crimean‐Congo haemorrhagic fever virus (CCHFV), six IgG serum samples, for Rickettsia spotted fever group ELISA (IgG), 13 serum samples and for Rickettsia typhus group ELISA, 15 serum samples. However, none of the patients that were orthohantavirus IgM positive had simultaneously antibodies against CCHFV, Rickettsia of spotted fever group and Rickettsia of typhus group (Abdiyeva et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A cross‐sectional descriptive study was set up in 2015–2016 among patients with FUO in Kazakhstan in the Almaty and the Kyzylorda region (Figure ). In these two regions, 13 hospitals were selected to conduct various studies in patients with FUO with a focus on rodent‐ and arthropod‐borne infections (Abdiyeva et al, ).…”
Section: Methodsmentioning
confidence: 99%